Effects of gases on optical properties of polyethylene glycol - Bilen, Bükem. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
Humidity induced changes in the refractive index and thickness of polyethylene glycol (PEG) thin films are in situ determined by optical waveguide spectroscopy. PEG brushes are covalently attached to the surface of a thin gold film on a BK7 glass using a grafting-from chemical synthesis technique. The measurements are carried out in an attenuated total reflection setup. At low humidity levels, both the refractive index and the thickness change gradually due to water intake and swelling of the PEG thin films. At around 80% relative humidity, a steep decrease in the refractive index and a steep increase in the thickness are observed as a result of a phase change from a semicrystalline state to a physical gel state. The hydrogenation of PEG films caused a less pronounced phase change from a semicrystalline state to a gel state. Moreover, the phase change is observed at around 85% relative humidity. Due to fewer ether oxygen atoms available for the water molecules to make hydrogen bonding, the polymer has a more stable structure than before and the phase change is observed at a higher humidity level. The response of PEG thin films exposed to various gases is also observed by optical waveguide spectroscopy. A decrease in the refractive index and an increase in the thickness are observed due to methanol, acetone and hexane exposure. However, no response to toluene and benzene vapors is observed. When exposed to xylene, an increase in the refractive index of PEG films and a decrease in the thickness are observed. The changes in the refractive index and thickness due to methanol absorption are observed to be greater than those of others, since the amounts of alcohols sorbed into the PEG films are greater than those of ketones, alkanes and aromatics.
Keywords: Polyethylene glycol.